Hardsurface layer of TiC embedded alloy steel by TIG torch technique - Maleque, Md. Abdul (2015)
Hardsurface layer was developed by tungsten inert gas (TIG) surface melting on AISI 4340 alloy steel with pre-placed TiC powder and energy input of 1344 J/mm in an argon gas environment. The composite coating layer was produced using an 80 A current, 35 volts potential difference and with a traversing speed reaching 1 mm /sec. The developed hardsurface was characterized in terms of surface condition, microstructure and hardness. The tribological behavior of the composite coating was evaluated using a pin on disc tribometer in Jatropha Curcas biodiesel. The surface appearance hard-faced layer was found to be free from any obvious defect. The TIG hard facing layer produced dendritic structure due to the dissolution of preplaced powder in the steel melt. The generated coating layer has a depth of 905 µm and 3.22 mm is the width of the track. The scanning electron microscope (SEM) analysis of the melt tracks reveals two common types of TiC, dendritic and cubic, precipitated in the steel matrix. The results showed that the incorporation of TiC particulate in the steel matrix increases the hardness and wear resistance by a factor of 3 and 2, respectively. The morphology of the wear tracks showed that the TiC particulates are strongly bonded to the substrate material giving the treated surface increased resistance to plastic deformation related to wear. The uncoated (low alloy steel) sample showed severe plastic deformation, micro-cracks, flake debris, and the presence of pitting corrosion due to the corrosive nature of biodiesel. Therefore, hard surface development on AISI 4340 steel with particulate TiC in the presence of TIG torch is an effective method for reducing corrosive wear in biodiesel environment.